Simultaneous improvement in strength and ductility in low carbon steel via intercritical annealing and quenching treatments. (2021) - Kumar Singh, Alok; Bhattacharya, Basudev; Biswas, Somjeet
Abstract: Hot-rolled low carbon steel sheets offer huge potential to be used in automotive body structures. Hot rolled steel sheets were subjected to intercritical annealing and quenching treatment to obtain high strength and ductility. Optical, scanning electron microscopy and X-ray diffraction were carried out to understand the underlying mechanisms. Microstructure and mechanical property correlation were established. High strength was achieved by increasing hard martensitic phase volume fraction in the soft ferrite matrix. Ductility was imparted by the ferrite matrix and martensite plasticity. Simultaneous improvements in strength and ductility were obtained by optimizing the ferrite-martensite microstructure during intercritical annealing and quenching.